THE ROLE OF INTEGRATED MARKETING COMMUNICATION ON INFLUENCING CONSUMER DECISION-MAKING - Vaid, Sanjay; Kumar, Dr. Ashish; Yadav, Dr. Priyanka (The journal of contemporary issues in business and government, 2023)
The research paper looks at how integrated marketing communication affects consumer decision- making. The study looks at how integrated marketing affects consumer decision-making using both qualitative and quantitative analysis. For qualitative analysis, we conduct a literature review and investigate previous work on the topic and articles published in books and journals. A reliability test confirms the validity of measurement scales with an above-average Cronbach’s alpha coefficient of 0.764, exceeding Nunnally’s (1978) threshold of 0.7. Variations are observed among the various components of IMC, revealing differential effects on decision-making. Certain scale items exhibit a high correlation (0.733) and an acceptable Cronbach Alpha value (0.732), while others exhibit a relatively low correlation (0.043) but still satisfactory Alpha values (0.776). In addition, the research reveals significant disparities in consumer perceptions of the credibility of e-commerce messages and the clarity of marketing communications. this highlights the need for organizations to prioritize clarity and credibility in IMC strategies in order to effectively guide CDM. The paper also reveals correlations between IMC and a series of consumer decision-making challenges, further reinforcing the central role of IMC in mitigating these issues.